The Role of the Supervisor of the Al-Amien Prenduan Islamic Boarding School Institute in Disciplining Students at the 2022 Boarding School Lectures - Muhammad Hafiz (Public Service: Jurnal Ilmu Sosial dan Pendidikan, 2025)
Translation science Role is an activity carried out by a person or an institution/organization. Islamic boarding schools have a very influential role in making intelligent and noble people, the presence of a caregiver in an Islamic boarding school is the highest leader in the organizational structure of the Islamic boarding school institution. The role of a caregiver is an important position for a caregiver in an Islamic boarding school. The caregiver in the Islamic boarding school is the main teacher and role model for the students. Because the caregiver is the one who is tasked with providing guidance, teaching, direction, and education to the students. This study aims to determine the role of caregivers in disciplining students in boarding school lectures and the caregiver's strategy in disciplining students in boarding school lectures. This study uses a descriptive qualitative research type, which was conducted at the Ma'had Institut Dirosat Islamiyah Al-Amien Prenduan. In this study, primary and secondary data were used which were collected from interviews, observations and documentation. The subjects of this study were the caregivers of the ma'had who played an important role in disciplining students. While the informants in this study were the Chancellor, Secretary General of the Ma'had and Academic Staff. The conclusion of the study is that the role of the caregivers of the Al-Amien Prenduan Islamic Boarding School Institute in disciplining students in the 2022 boarding school lectures are: The caregiver as an example, the role of the caregiver as a motivator, the role of the caregiver as an instructor, the role of the caregiver as a header. and the strategies of the caregivers of the Al-Amien Prenduan Islamic Boarding School Institute in disciplining students in the 2023 boarding school lectures are: Monitoring intensively, giving examples, preaching.